Economic sociology in Singapore: Meritocracy and the missing embeddedness - Vincent Chua (economic sociology. perspectives and conversations, 2021)
Singapore can be described as a "developmental state," defined by Chalmers Johnson as a state focused on economic development and which takes necessary policy actions to accomplish this objective. He writes specifically about Japan and the role of the economic agency MITI (Ministry of International Trade and Industry) in ushering in the Japanese miracle, but there are striking parallels to the four Asian tigers: South Korea, Taiwan, Singapore, and Hong Kong. Johnson says, "In states that were late to industrialize, the state itself led the industrialization drive, that is, it took on developmental functions" (Johnson 1982, 19). Like other Asian tigers, Singapore is known for its exceptional economic growth, and the state played a critical role in this growth. What distinguishes it from the other Asian economies, however, is the singular focus the state has placed on meritocracy to achieve it. In a study of thirty-five countries, Peter Evans and James Rauch (1999) devised a "Weberian scale" to describe the extent to which formal mechanisms and meritocratic procedures are applied to the recruitment of government officials, with special attention to the selection of public sector bureaucrats through a national examination system. They put meritocracy scores on the x-axis and correlate them with a measure of GDP to represent economic growth on the y-axis. The graph, which I reproduce here but with GDP scores updated to reflect 2019 conditions (Figure 1), shows an upward sloping line, suggesting a positive relationship between meritocracy and economic growth. Of special interest to me, Singapore is situated at the upper right-hand corner of this graph, indicating that its high levels of meritocracy play a substantial role in its exceptional economic growth. (...)
Keywords: 300